Forces exerted on the back during jumping in horses - Stanton, S.; Peters, D.; Lavagnino, M.; Bidwell, L.; Manfredi, J. (Journal of Equine Veterinary Science, 2021)
Back pain in hunter/jumper equine athletes can affect performance and welfare. The study's objective was to compare the pressure placed on a horse's back during the phases of takeoff, flight, and landing at various jump heights. We hypothesized that there would be greater forces exerted with increased jump height and during the landing phase. A Pliance-s mat collected pressure data from 5 horses and 3 riders at the canter and over obstacles of set heights (0.84 m and 1m) and was synchronized with video to analyze average mean or peak pressures from the whole, front, and back of the mat. Pressures during the phases were normalized to the canter baseline to control for differences between horse-rider combinations. Statistics included a repeated measures ANOVA with Šídák's multiple comparisons tests (significant at P < 0.05). There was no significant difference in pressures seen between jump heights. The mean pressures during takeoff and landing were not significantly different from each other but were significantly greater than flight (all P < 0.05). Peak pressure of the whole pad and mean pressures of both the front and back of the pad during takeoff and landing were greater than during flight, and landing peak pressure was greater than takeoff (P < 0.05). Relating jumping phases with quantitative pressure results may aid in further understanding of the cause and subsequent prevention of back-related performance issues.